Is external control important for internal control? - Busseniers, Evo (Journal of Sociocybernetics, 2016)
In cybernetics, the basic assumption is that systems aim for control.But what and how are they controlling? I dierentiate two categories ofcontrol: internal and external control. In external control, one starts fromoutside, and tries to determine the environment completely. While withinternal control, one's own aspirations are taken as a starting point, anduseful synergies with the environment are sought. I'll dene these con-cepts in cybernetic terms, and argue why they are not necessary related.There are two aspects in this dierence. The rst lies in the locality: isthere an aim for global control, or only for control in the immediate envi-ronment? There is also a dierence in what one tries to change. An agentcould adapt its links, or try to change either the methods or the goals ofits neighbors.Several of these cases will be further explored by giving an existing modelthat falls under this circumstances. All of these models will be put intoan overarching framework. The model of controllability is a model aboutglobal control, while the others model local control, based on neural net-works or perceptual control theory.